The construction of Costa Rican ideology by the Catholic Church hierarchy, 1850-1920. - Sandí, José Aurelio (2013)
The main purpose of this article is to reveal how the Roman Catholic Clergy of 1850-1920 collaborated with the State in molding, transmitting and consolidating the ideology that gives expression to the sense of Costa Rican-ness. This action was carried out with the intervention of the Catholic priests located in the different communities of the country, who were responsible for implementing the mandates jointly agreed upon by the Church and the State.The Roman Catholic Clergy established that those individuals that wished to be legally recognized as Costa Rican citizens should meet the following requirements: obey the established law and order; support and defend the State, its institutions and its political agreements;respect certain public sanitary dispositions; respond to an educational system proposed by the government and the Church; defend the country, its liberty, its religion, the institution of the family, and the country’s patrimony in times of international conflicts. Finally, the Church established that Costa Ricans should always manifest Christian charity. The article explains the way in which the Roman Catholic Church disseminated these norms among the people and how this ideology served to the interest of both, the Church and the civil government